The Stockholm congestion – charging trial 2006: Overview of effects - Eliasson, Jonas; Hultkrantz, Lars; Nerhagen, Lena; Rosqvist, Lena Smidfelt (Transportation research. Part A, Policy and practice, 2009)
The Stockholm congestion charging trial in 2006 demonstrated the effects of a full-scale time-differentiated urban road toll scheme. Improvements in travel times were large enough to be perceived by the general public. This was pivotal to the radical change of public attitudes that occurred during the trial and that resulted in a positive outcome of a subsequent referendum on a proposal for making the system permanent. This paper summarises the effects of the trial and analyses to what extent targets were met. Effects on congestion reduction were larger than anticipated, which also resulted in favourable economic and environmental effects. The trial showed that a single-cordon toll could affect traffic within a large area, i.e., not just close to the zone limits.